Discussion on the Securities Law 2019: Amended and supplemented in 2024 of Vietnam regarding the regulations on the conditions for the initial public offering of shares compared to the regulations of some countries in the region - Tam, Nguyen Thanh (Edelweiss Applied Science and Technology, 2025)
In the process of international economic integration, in 2018, Vietnam became the largest IPO market in Southeast Asia. Therefore, the Securities Law must change for good and effective management. The provisions of the Initial Public Offering conditions in the Securities Law of 2019 ensure the interests of investors, increase the trust of issuers, and enhance the stability of the stock exchange market in today’s era. This article aims to delve into Clause 1, Article 15 of the Securities Law of 2019, analyzing its specific provisions and evaluating the positive and negative impacts of these regulations. Furthermore, it offers a comparative perspective by examining how these changes measure up against IPO regulations in other countries across Southeast Asia. By exploring the nuances of these regulatory adjustments, this analysis sheds light on Vietnam’s progress in modernizing its legal framework while identifying areas for potential refinement to ensure the continued growth and competitiveness of its stock market. Through this approach, Vietnam is well-positioned to balance the interests of investors and issuers while maintaining a market environment that supports innovation, inclusivity, and sustainable economic development.